Respuesta :
Answer:
x=0, 2. y=-1, 5.
Step-by-step explanation:
y=(1/2)x^2+2x-1
3x-y=1
---------------------
3x-y=1
y=3x-1
-----------
(1/2)x^2+2x-1=3x-1
(1/2)x^2+2x-3x-1-(-1)=0
(1/2)x^2-x-1+1=0
(1/2)x^2-x=0
factor out the x
x[(1/2)x-1]=0
zero property,
x=0, (1/2)x-1=0
-------------------
(1/2)x-1=0
1/2x=0+1
1/2x=1
x=1/(1/2)=(1/1)(2/1)=2/1=2
-----------------------------------
x=0, x=2
-------------
y=(1/2)(0)^2+2(0)-1=0+0-1=-1
-------------
y=3(0)-1=0-1=-1
-----------------------
y=(1/2)(2)^2+2(2)-1=(1/2)(4)+4-1=4/2+4-1=2+4-1=6-1=5
----------------------
y=3(2)-1=6-1=5
Answer:
The solutions are (0, -1) and (2, 5)
Step-by-step explanation:
y = (1/2)x^2 + 2x - 1 ------ eqn(I)
3x - y = 1
y = 3x - 1 ------------- eqn(II)
Equate eqn(I) & (II)
(1/2)x^2 + 2x - 1 = 3x - 1
Multiply each term by 2
x^2 + 4x - 2 = 6x - 2
x^2 + 4x - 6x = -2 + 2
x^2 - 2x = 0
x(x - 2) = 0
x = 0, 2
Substitute the values of x in eqn(II)
y = 3x - 1
When x = 0
y = 3(0) - 1 = 0 - 1 = -1
y = 3x - 1
When x = 2
y = 3(2) - 1 = 6 - 1 = 5
The solutions are (0, -1) and (2, 5)